Assessment of spermicidal activity of the antimicrobial peptide sarcotoxin Pd: A potent contraceptive agent. (2nd January 2016) - Zare-Zardini, Hadi; Fesahat, Farzaneh; Anbari, Fatemeh; Halvaei, Iman; Ebrahimi, Leila
Abstract : Objectives In searching for new spermicidal microbicides for use in the prevention of unplanned pregnancy and sexually transmitted infections (STIs) we investigated the spermicidal and cytotoxicity activities of the antimicrobial peptide sarcotoxin Pd. Methods Washed sperm from 10 healthy, normal volunteers was treated with different concentrations of sarcotoxin Pd. Sperm motility and morphology were assessed at 0, 0.3, 5, 10 and 15 min. The cytotoxicity of sarcotoxin Pd in normal human cervical HeLa cells was measured. Percentage cell survival was expressed as the number of live cells in the test group. Results The cytotoxic effect of sarcotoxin Pd was concentration-dependent. Significant cytotoxicity was observed at concentrations above 24 μg/ml. Sarcotoxin Pd immobilised 100% of spermatozoa at a dose of 90 and 80 μg/ml after 0.3 and 5 min, respectively, and immobilised 50% of spermatozoa after 15 min at lower doses. Sarcotoxin Pd inhibited sperm motility in a dose-dependent manner. The peptide immobilised sperm within 20 s at its maximal effective concentration of 90 μg/ml. Conclusions Sarcotoxin Pd appears to be a good candidate for a contraceptive agent in the prevention of unplanned pregnancy and STIs. Abstract : 摘要 目的 为了寻找一种同时具有杀精子活性和抗菌活性的药物，既能防止非计划妊娠又能预防性传播疾病，我们对抗菌肽sarcotoxin Pd的杀精子活性和细胞毒性进行了研究。 方法 从10名健康的志愿者获得精液，洗涤后分别与不同浓度抗菌肽sarcotoxin Pd的液体进行混合。分别记录混合后0、0.3、5、10和15分钟时间间隔的精子形态和活动度。通过测定正常人宫颈HeLa细胞在含有不同浓度的抗菌肽sarcotoxin Pd培养基里进行培养后的活细胞数来反映其细胞毒性。 结果 抗菌肽sarcotoxin Pd的细胞毒性是浓度依赖性的。24ug/ml以上浓度的抗菌肽sarcotoxin Pd具有显著的细胞毒性。抗菌肽sarcotoxin Pd的杀精子活性在90ug/ml浓度0.3分钟以及80ug/ml浓度5分钟后可以使100%的精子失去活性，而较低的浓度则需要超过15分钟来使50%的精子失去活性。抗菌肽sarcotoxin Pd对精子活动度的影响也是剂量依赖性的。抗菌肽sarcotoxin Pd的最大有效浓度90ug/ml能够在20秒内让精子失去活性。 结论 抗菌肽sarcotoxin Pd看起来是既能防止非计划妊娠又能预防性传播疾病的避孕方法的一种不错的选择。